Optimization of Crospovidone and Copovidone in Fast Disintegrating Tablet (FDT) Diphenhydramine HCl Using Factorial Design - Agatha Budi Susiana Lestari; Aldo Christian Jonathan (Sanata Dharma University, 2023)
Diphenhydramine HCl is a drug used to treat motion sickness. Treatment of motion sickness needs rapid onset for successful therapy. Fast Disintegrating Tablet (FDT) is one dosage form that provides fast onset. The purpose of this study was to identify the dominant factors of crospovidone and copovidone, their interactions, and discover the optimum composition area to produce a FDT dosage form with optimum parameters involving hardness, friability, disintegration time, wetting time, and water absorption ratio. This study was experimental and used a factorial design. The result showed that copovidone significantly influenced friability, disintegration time, wetting time, and water absorption ratio, while their interactions significantly influenced the hardness of FDT diphenhydramine HCl. At the level studied, the optimum composition area was found, which can be predicted as a diphenhydramine HCl FDT dosage form formula.